2019
DOI: 10.1093/jb/mvz034
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of miR484-TUSC5 axis takes part in the progression of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. miR-484 is previously reported to be a crucial modulator during the process from precancerous lesion to cancer. Tumour suppressor candidate 5 (TUSC5) is a potential tumour suppressor, but its expression and function in HCC are obscure. In this study, we aimed to explore the roles of miR-484 and TUSC5 in HCC, and clarify the relationship between them. We demonstrated that miR-484 was significantly up-regulated in HCC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…It also has been reported that miR-484 was highly specific for prostate cancer, which could make it act as a prostate cancer screening biomarker [35]. In hepatocellular carcinoma, miR-484 has an oncogenic role by targeting TUSC5 [36]. Moreover, miR-484 could act as the biomarker for many other cancers, including lung cancer, breast cancer, cervical cancer and colorectal cancer [15,16,37].…”
Section: Discussionmentioning
confidence: 97%
“…It also has been reported that miR-484 was highly specific for prostate cancer, which could make it act as a prostate cancer screening biomarker [35]. In hepatocellular carcinoma, miR-484 has an oncogenic role by targeting TUSC5 [36]. Moreover, miR-484 could act as the biomarker for many other cancers, including lung cancer, breast cancer, cervical cancer and colorectal cancer [15,16,37].…”
Section: Discussionmentioning
confidence: 97%
“…31 In tumours, the expression of some miRNAs was inhibited, and the binding of miRISC to the 3′-UTR of target genes was reduced, resulting in the release of translation inhibition of downstream target genes. It has been reported that miR-484 can target the expression of Apaf-1, ZEB1, SMAD2 and TUSC5, [13][14][15]32 thus affecting the occurrence and development of tumours. Bioinformatics software is an important tool for predicting target genes of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that miR-484 may participate in NSCLC development. It is worth noting that miR-484 expression differs in different cancers: in liver cancer, miR-484 expression is significantly upregulated, but it is significantly decreased in gastric cancer [25,26]. This shows that miR-484 has diverse roles that are determined by the type of tumor, miRNA localization, and its target genes.…”
Section: Discussionmentioning
confidence: 99%